The Elephant in the Room: Addressing Student Mental Health at McMaster University - Kurdina, Anna; Kilian, Alexandra; Jin, Shicheng (Tony) (The Meducator, 2016)
The McMaster Health Forum strives to be a leading hub for improving health outcomes at the regional and provincial level in Canada. Through problem-solving and discussion, they harness information, convene stakeholders, and prepare action-oriented leaders to meet pressing health issues creatively.